PENGARUH PENGELOLAAN KEARSIPAN TERHADAP EFISIENSI KERJA PEGAWAI KANTOR KECAMATAN NUSANIWE - Dirga Haumahu; Ambarwati Soetiksno; Wylda O. Kowey (Jurnal Administrasi Terapan, 2023)
Records management is one of the most important things to achieve work efficiency. good and good archive management will certainly encourage increased work efficiency. This study aims to measure the effect of archive management on the work efficiency of the employees of the Nusaniwe Ambon District Office. The problems faced by the Nusaniwe Ambon District Office are: Based on the observations of archiving officers who are not careful in storing archives so that archive officers have difficulty finding archives, the Filing Cabinet Facility which is used to store archives at the Nusaniwe Ambon District office is used to put glasses and cloth napkins. In terms of salvage many files are not secured, files are left piled up on the floor. Likewise with archives that have been unused for years and are left piled up without any follow-up from the archivist to destroy them. This research is a quantitative research supported by descriptive. The method of data collection is by using a questionnaire. The population in this study amounted to 20 with a sample of 7 people. The sampling technique used is purposive sampling. From the results of statistical research on archive management, it has a positive and significant effect on the work efficiency of the employees of the Nusaniwe Ambon District Office. This is evidenced by the value of the archive management variable coefficient of 7.539 and the significant value of the discipline variable of 0.01 which is smaller than 0.05, meaning that with good archive management, employee work efficiency will increase. In conclusion, archive management has a positive and significant effect on the work efficiency of the employees of the Nusaniwe Ambon District Office, there is a correlation coefficient value of x to variable y of 0.959 with a very strong category. And Suggestions, the Nusaniwe Ambon District Office, especially the archive management section, should be able to implement a good Archives Management plan, so that it can help overcome several problems related to the existing Archives Management. That way, employee work efficiency can be improved because of the ease in the process of carrying out work. Keywords: Records Management, Employee Work Efficiency